Phenotypic and microRNA transcriptomic profiling of the MDA-MB-231 spheroid-enriched CSCs with comparison of MCF-7 microRNA profiling dataset - Boo, L.; Ho, W.Y.; Ali, N.M.; Yeap, S.K.; Ky, H.; Chan, Kok Gan; Yin, W.F.; Satharasinghe, D.A.; Liew, W.C.; Tan, S.W.; Cheong, S.K.; Ong, H.K.A. (PeerJ, 2017)
Breast cancer spheroids have been widely used as in vitro models of cancer stem cells (CSCs), yet little is known about their phenotypic characteristics and microRNAs (miRNAs) expression profiles. The objectives of this research were to evaluate the phenotypic characteristics of MDA-MB-231 spheroid-enriched cells for their CSCs properties and also to determine their miRNAs expression profile. Similar to our previously published MCF-7 spheroid, MDA-MB-231 spheroid also showed typical CSCs characteristics namely self-renewability, expression of putative CSCs-related surface markers and enhancement of drug resistance. From the miRNA profile, miR- 15b, miR-34a, miR-148a, miR-628 and miR-196b were shown to be involved in CSCsassociated signalling pathways in both models of spheroids, which highlights the involvement of these miRNAs in maintaining the CSCs features. In addition, unique clusters of miRNAs namely miR-205, miR-181a and miR-204 were found in basal-like spheroid whereas miR-125, miR-760, miR-30c and miR-136 were identified in luminallike spheroid. Our results highlight the roles of miRNAs as well as novel perspectives of the relevant pathways underlying spheroid-enriched CSCs in breast cancer.